Manejo de plantaciones de cacao CCN-51 y su influencia en los factores biológicos de unidades agrícolas del cantón la Troncal, Provincia de Cañar, Ecuador. - Villa Muñoz, Wilmer Alfredo (2018)
The study was based on the evaluation of the management of cocoa plantations CCN-51 in the biological factors of agricultural units of the canton La Troncal. The objectives of the study were: to identify the management conditions of the CCN-51 cocoa plantations in the localities: Alipio (Manuel de J Calle), Las Cañas (Cochancay) and El Rosario (La Puntilla) of the La Troncal canton, characterize the main environmental impacts produced by the management of cocoa plantations CCN-51 and propose agroecological measures tending to the mitigation, reduction and compensation of the identified environmental impacts. The research methodology included the execution of the following activities: surveys of small and medium cocoa producers in the rural area of La Troncal, collection and analysis of soil samples, statistical analysis of the surveys carried out, impact assessment environmental. The research instruments used were: Likert questionnaire, observation sheet, SWOT matrix, impact identification matrix, impact characterization matrix of Leopold. The statistical software used was Minitab 15. The results show that the management of the cocoa crop is carried out in a conventional manner; the items that discriminate the questionnaire of the survey were P1, P8, P15 and P16 because they have the most representative values of coefficient r, t Student and the Friedman test to 95%; The environmental impacts derived from the management of cocoa plantations CCN-51 mostly affect vertebrate and invertebrate factors, landscape, soil quality, plant cover and human health. Keywords: Agriculture, Agroecology, Cacao CCN-51, Environmental Impact, Agricultural Unit